Sea Sirens - Chu, Amy (Chu, Amy. Trot & Cap'n Bill adventure., 2019)
Inspired by the L. Frank Baum adventure, a young girl named Trot is supposed to be caring for her dementia-inflicted grandfather but decides to go surfing instead and nearly drowns trying to save her cat, Captain Bill. She is saved at the last minute by a group of magical Sirens who entreat Trot to help with an underwater crisis. She brings her grandfather with her and along with Captain Bill, the trio help the Sirens before it's time to return to land.